Cognitive developmental levels of preschool children in relation to peer relationships - (:unkn) unknown (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2015)
The purpose of the study is to investigate the cognitive developmental levels of five- to six-year-old preschool children with regard to their peer relationships. The relational survey method was used in the study. One hundred and fifty one children aged five- to six-years-old participated in the study. The Child Behaviour Scale, Peer Victimisation Scale and the Marmara Developmental Scale-Cognitive Development subscale were filled out by preschool teachers. The data was analysed using the Basic Linear Regression Technique. According to the results of the study, five- to six-year-old children's cognitive development levels have a significant predictor on variables of peer relationship.
Keywords: cognitive development; peer relationships; victimisation; preschool children; BEHAVIOR; GENDER; MIND